Osteoclast differentiation and bone resorption in multicentric reticulohistiocytosis. - Adamopoulos, I; Wordsworth, P; Edwards, J; Ferguson, D; Athanasou, N (2006)
Multicentric reticulohistiocytosis (MR) is a systemic disease of unknown cause characterized by the presence of a heavy macrophage infiltrate in skin and synovial tissues and the development of an erosive polyarthritis. The synovial fluid in MR is known to contain numerous mononuclear cells. In this study, we have determined whether these cells contribute to joint destruction in MR by differentiating them into osteoclasts. Synovial fluid mononuclear cells were isolated from the knee joint of a 44-year-old male with MR. These cells were cultured with various combinations of macrophage-colony stimulating factor, receptor activator for nuclear factor kappaB ligand (RANKL), tumor necrosis factor alpha, interleukin-1alpha, osteoprotegerin, and zoledronate. Osteoclast differentiation was assessed by expression of tartrate-resistant acid phosphatase, vitronectin receptor, and the extent of lacunar resorption. Most MR synovial fluid mononuclear cells expressed a macrophage phenotype (CD14(+), CD68(+), HLA-DR(+), CD11b(+)). Extensive osteoclast formation and lacunar resorption were noted in macrophage-colony stimulating factor/RANKL-treated cell cultures. MR synovial fluid contained increased tumor necrosis factor alpha and decreased osteoprotegerin compared with osteoarthritis synovial fluid. Lacunar resorption was inhibited in cultures containing zoledronate. Pamidronate treatment of the patient also reduced the number of synovial fluid macrophages and resulted in less osteoclast formation and lacunar resorption. MR synovial fluid contains numerous macrophages that are capable of differentiating into osteoclasts by the RANKL signaling pathway. Inhibitors of osteoclast formation and resorption activity may be of use in preventing the severe joint destruction that commonly occurs in MR.